Investigating the Link Between Chronic Health Conditions and Mental Health Symptoms Among Low-income Patients Seen at a Student-Run Free Clinic - Samuel Vincent; Marianne Chirica; Jyothirmayi Thippana; Melissa Chen; Kristin Schneider (Journal of Student-Run Clinics, 2024)
Background: Individuals with chronic health conditions (CHCs) experience more anxiety and depression symptoms than those without CHCs. However, there is a dearth of research examining these relationships among low-income and minoritized populations. This current study investigated whether specific CHCs (i.e., diabetes, hypertension, hyperlipidemia) are linked to greater depression and anxiety symptoms among low-income, uninsured, and primarily Latine adults seen at a student-run free clinic (SRFC).Methods: Participants were 149 adults (aged 19-78 years) seen at a SRFC serving low-income community members. Participants were primarily female (63.0%) and Spanish-speaking (67.0%). Anxiety and depressive symptoms were measured using the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9). The presence of CHCs were extracted from participant medical records.Results: The presence of CHCs were associated with lower anxiety symptoms and the presence of hypertension and hyperlipidemia were linked to lower depression symptoms.Conclusions: Overall, this study demonstrates the importance of investigating relationships between mental and physical health conditions using understudied samples as findings observed among mostly White, higher income samples may not generalize. Research conducted in SRFCs may improve knowledge of understudied populations, such as low-income and ethnically diverse patients. Cultural factors may have contributed to these unexpected results (e.g., stigma-related underreporting of mental health symptoms, inadequate methods to assess culture-specific symptoms). These findings suggest the need for future research to explore alternative methods of assessing mental health symptoms among low income, ethnically diverse populations.